Examining teachers' attitudes and practices of special education in Kansas during COVID-19 - Fugate, Adele Doris (Kansas State University, 2022)
Prior to COVID-19, elementary and secondary education teachers worked with an ever-changing education program developed to meet the educational needs of students with disabilities. COVID-19 created an environment of uncertainty in teaching masked students with special needs in either face to face, or remote learners or a hybrid of the two methodologies. The study measured the attitudes and practices of elementary and secondary special education teachers toward teaching students with disabilities during COVID-19 in Kansas. Elementary and secondary special education teachers have had a complex and tumultuous professional relationship toward adequate preparation to provide the legally stated goals in an Individual Education Program and inclusion required for the Least Restrictive Environment. The COVID-19 pandemic also presented special conditions that varied from amongst national leadership, state to state, and the specific local district superintendents and local building principals. Ultimately, this study researched what attitudes and practices towards special education special education teachers in Kansas experienced during COVID-19. The study also addressed what modalities were used to meet IEP goals during COVID-19. Finally, the study quantified the use of the three main methods of instruction for students with special needs during COVID: face-to-face, remote or a hybrid of the two methods.
Keywords: Special education teachers during COVID-19